Chinese Imports : What's Behind the Slowdown? - Kang, Joong (IMF Working Papers; Working Paper ;, 2016)
Real imports in China have decelerated significantly over the last two years to below 4 percent (yoy) from double-digit growth in previous years. Weaker investment, partly due to progress in rebalancing from investment to consumption, has been the main factor accounting for about 40-50 percent of slowdown during this period. Weaker exports also account for about 40 percent of slowdown, of which about a quarter is due to stronger RMB. Onshoring-substitution of imported intermediate inputs with domestic production-has not been an additional drag over this period but it continues to slow import growth at a similar pace as previous periods. There is large uncertainty about the impact of rebalancing on the import slowdown due to difficulties in identifying the counterfactual nonrebalancing path.